Exercise training improves relaxation response and SOD-1 expression in aortic and mesenteric rings from high caloric diet-fed rats - Moraes, Camila de; Davel, Ana Paula Couto; Rossoni, Luciana Venturini; Antunes, Edson; Zanesco, Angelina (Springer Nature, 2008)
Background. Obesity has been associated with a variety of disease such as type II diabetes mellitus, arterial hypertension and atherosclerosis. Evidences have shown that exercise training promotes beneficial effects on these disorders, but the underlying mechanisms are not fully understood. The aim of this study was to investigate whether physical preconditioning prevents the deleterious effect of high caloric diet in vascular reactivity of rat aortic and mesenteric rings. Methods. Male Wistar rats were divided into sedentary (SD); trained (TR); sedentary diet (SDD) and trained diet (TRD) groups. Run training (RT) was performed in sessions of 60 min, 5 days/week for 12 weeks (70-80% VO2max). Triglycerides, glucose, insulin and nitrite/nitrate concentrations (NOx -) were measured. Concentration- response curves to acetylcholine (ACh) and sodium nitroprusside (SNP) were obtained. Expression of Cu/Zn superoxide dismutase (SOD-1) was assessed by Western blotting. Results. High caloric diet increased triglycerides concentration (SDD: 216 ± 25 mg/dl) and exercise training restored to the baseline value (TRD: 89 ± 9 mg/dl). Physical preconditioning significantly reduced insulin levels in both groups (TR: 0.54 ± 0.1 and TRD: 1.24 ± 0.3 ng/ml) as compared to sedentary animals (SD: 0.87 ± 0.1 and SDD: 2.57 ± 0.3 ng/ml). On the other hand, glucose concentration was slightly increased by high caloric diet, and RT did not modify this parameter (SD: 126 ± 6; TR: 140 ± 8; SDD: 156 ± 8 and TRD 153 ± 9 mg/dl). Neither high caloric diet nor RT modified NO x - levels (SD: 27 ± 4; TR: 28 ± 6; SDD: 27 ± 3 and TRD: 30 ± 2 μM). Functional assays showed that high caloric diet impaired the relaxing response to ACh in mesenteric (about 13%), but not in aortic rings. RT improved the relaxing responses to ACh either in aortic (28%, for TR and 16%, to TRD groups) or mesenteric rings (10%, for TR and 17%, to TRD groups) that was accompanied by up-regulation of SOD-1 expression and reduction in triglycerides levels. Conclusion. The improvement in endothelial function by physical preconditioning in mesenteric and aortic arteries from high caloric fed-rats was directly related to an increase in NO bioavailability to the smooth muscle mostly due to SOD-1 up regulation. © 2008 de Moraes et al; licensee BioMed Central Ltd.
Keywords: acetylcholine; copper zinc superoxide dismutase; glucose; insulin; nitrate; nitrite; nitroprusside sodium; triacylglycerol; superoxide dismutase; animal experiment; animal food; aorta; caloric intake; control group; controlled study; exercise; food intake; male; mesentery; nonhuman; rat; relaxation training; Western blotting; animal; fat intake; mesenteric artery; metabolism; methodology; physiology; vascular endothelium; vasodilatation; Wistar rat; Animals; Aorta; Dietary Fats; Endothelium, Vascular; Energy Intake; Male; Mesenteric Arteries; Physical Conditioning, Animal; Rats; Rats, Wistar; Superoxide Dismutase; Vasodilation